Reading the Irish Woman Studies in Cultural Encounters and Exchange, 1714-1960 - Meaney, Gerardine (Reappraisals in Irish History, 2013)
The theme of this book is cultural encounter and exchange in Irish women's lives. Using three case studies: the Enlightenment, emigration and modernism, it analyses reading and popular and consumer culture as sites of negotiation of gender roles. It traces how the circulation of ideas, fantasies and aspirations which have shaped women's lives in actuality and in imagination and argues that there were many different ways of being a woman. Attention to women's cultural consumption and production shows that one individual may in one day identify with representations of heroines of romantic fiction, patriots, philanthropists, literary ladies, film stars, career women, popular singers, advertising models and foreign missionaries. The processes of cultural consumption, production and exchange provide evidence of women's agency, aspirations and activities within and far beyond the domestic sphere.